Assessing the Mental Health of Fathers, Other Co-parents, and Partners in the Perinatal Period: Mixed Methods Evidence Synthesis - Darwin, Zoe; Domoney, Jill; Iles, Jane; Bristow, Florence; Siew, Jasmine; Sethna, Vaheshta (Frontiers in Psychiatry, 2021)
Introduction: 5-10% of fathers experience perinatal depression and 5-15% experience perinatal anxiety, with rates increasing when mothers are also experiencing perinatal mental health disorders. Perinatal mental illness in either parent contributes to adverse child and family outcomes. While there are increasing calls to assess the mental health of both parents, universal services (e.g. maternity) and specialist perinatal mental health services usually focus on the mother (i.e. the gestational parent). The aim of this review was to identify and synthesize evidence on the performance of mental health screening tools and the acceptability of mental health assessment, specifically in relation to fathers, other co-parents and partners in the perinatal period. Methods: A systematic search was conducted using electronic databases (MEDLINE, PsycINFO, Maternity & Infant Care Database and CINAHL). Articles were eligible if they included expectant or new partners, regardless of the partner's gender or relationship status. Accuracy was determined by comparison of screening tool with diagnostic interview. Acceptability was predominantly assessed through parents’ and health professionals’ perspectives. Narrative synthesis was applied to all elements of the review. Results: Seven accuracy studies and 20 acceptability studies were included. The review identified that existing evidence focuses on resident fathers and assessing depression in universal settings. All accuracy studies assessed the Edinburgh Postnatal Depression Scale but with highly varied results. Evidence on acceptability in practice is limited to postnatal settings. Amongst both fathers and health professionals, views on assessment are mixed. Identified challenges were categorized at the individual-, practitioner- and service-level. These include: gendered perspectives on mental health; the potential to compromise support offered to mothers; practitioners’ knowledge, skills and confidence; service culture and remit; time pressures; opportunity for contact; and the need for tools, training, supervision and onward referral routes. Conclusion: There is a paucity of published evidence on assessing the mental health of fathers, co-mothers, step-parents and other partners in the perinatal period. Whilst practitioners need to be responsive to mental health needs, further research is needed with stakeholders in a range of practice settings, with attention to ethical and practical considerations, to inform the implementation of evidence-based assessment.